(untitled) (Revista Argentina de Musicología, 2012)
This article starts with an idea that emerged during the 52nd International Congress of Americanists in Seville, 2006, where I participated as a speaker at the symposium Cosmologies and their representations in images, discourses, rituals and music in the Central Andes. Impressed by the lectures of Jürgen Golte3 and Rodolfo Sánchez Garrafa4, I imagined that the applicability of the Andean cosmology could go beyond what usually supposed, and could be underlying the interpretation not only of pre-Columbian instruments such as the highland siku but also of European instruments brought to the Andean region by the conquerors as the single-strung harp. Here I show the possible application of Andean cosmological aspects in the organology, construction and performance technique of the Andean harp, supplementing with observations on the Andean pentatonic and European diatonicism as dialectical elements.